2019
DOI: 10.1177/2150132719887260
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Social Determinants of Health Screening at Community Health Centers: Clinician and Staff Perspectives

Abstract: Purpose: Screening for social determinants of health (SDOH) during primary care office visits is recommended by pediatric and internal medicine professional guidelines. Less is known about how SDOH screening and service referral can be successfully integrated into clinical practice. Methods: Key informant interviews with 11 community health center (CHC) clinicians and staff members (medical assistants and case managers) were analyzed to identify themes related to integrating a SDOH screening and referral proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 16 publications
(36 reference statements)
2
48
0
Order By: Relevance
“…The remainder reported using observational study designs (eg, pre-post studies, feasibility studies, pilot studies). Fifty-eight studies were conducted with primary care patients, [29][30][31][72][73][74]76,[78][79][80][81][82][83][84][85][86][87][88][89] 4 took place in a specialty clinics, 32,71,75,77 1 took place in urgent care, 27 and 3 took place across multiple settings (eg, primary, specialty, and urgent care). 26,28,90 Majority of studies reported including academic sites (n = 40), 29,[34][35][36][37][38][39][41][42][43][44][47][48][49][50][51][52][53][54][55][56]…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…The remainder reported using observational study designs (eg, pre-post studies, feasibility studies, pilot studies). Fifty-eight studies were conducted with primary care patients, [29][30][31][72][73][74]76,[78][79][80][81][82][83][84][85][86][87][88][89] 4 took place in a specialty clinics, 32,71,75,77 1 took place in urgent care, 27 and 3 took place across multiple settings (eg, primary, specialty, and urgent care). 26,28,90 Majority of studies reported including academic sites (n = 40), 29,[34][35][36][37][38][39][41][42][43][44][47][48][49][50][51][52][53][54][55][56]…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
“…29,30,32,65,68,71 Six articles did not report the workforce for self-administered screening. 34,42,54,56,59,81 In 10 of 37 models that used self-administered screening, the medical assistants, nurses, navigators, resource specialists, and research staff who provided patients with the screening form also reviewed the screen to provide assistance. 32,43,53,65,68,69,71,73,80,82 While these staff were the first to provide assistance to patients, many still referred patients to other staff for additional assistance.…”
Section: Screening and Responding To Unmet Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the organizational level, health care delivery systems tailored to meet the needs of the homeless have been found to be the most successful in improving primary care access for this population. 44 Some promising recent approaches focus on social determinants of health screening 45 and the colocation of services that offer medical and social care, 46 such as a homeless-tailored primary care clinic and ED 47 and nurseled primary health clinic and men's shelter. 7 Organizations that have reported success integrating care services share the traits of prioritizing vulnerable populations, extensive community collaboration, team approaches, diversified funding, and being data driven.…”
Section: Mental Illnessmentioning
confidence: 99%
“… 8 Evidence suggests that providers understand the value of social needs screening, but find it logistically and ethically challenging, particularly when unable to easily connect patients with needed assistance. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%